Wafer as an adjunct to plating patient-specific implants for the multi-segment maxilla: a useful tool. Issue 8 (August 2022) - Wang, R.; Choi, W.S.
Abstract: Virtual surgical planning for orthognathic surgery using patient-specific implants (PSI) is usually waferless nowadays. However, without an occlusal wafer, difficulties arise in controlling the accuracy of multi-segment maxillary osteotomies, especially for expansion and rotational movements of each segment. It is technically challenging intraoperatively to manipulate multiple segments to fit into the PSI, as the relatively small bone segments need to be secured into the PSI while simultaneously achieving individual segment movements in all planes and with potential bony interferences with each other. Therefore, the use of a maxillary tooth-supported surgical guide is proposed and described. When the guide is inserted before the PSI, it overcomes difficulties in handling multiple maxillary segments and facilitates achieving maximal positional precision of each individual bone segment. The guide enables multiple smaller segments to behave as one unit with the designated occlusion whilst visualizing bony interferences before PSI plating is commenced. Adding a tooth-borne surgical guide in the form of a wafer and a customized arch bar is a cost-effective method to enhance accuracy in virtually planned multi-segment maxillary surgery. Further investigations are required to validate the accuracy and advantages of using wafers and PSI in multi-segment maxillary and mandibular orthognathic surgeries.